THE ABILTY OF THE SECOND GRADE STUDENTS OF MA DARUL ISTIQOMAH KEMUNING INHIL IN WRITING RECOUNT TEXTS - Nurjannah Indriani; Eliwarti Eliwarti; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This descriptive quantitative research was aimed to find out the ability of the second grade students of MA Darul Istiqomah Kemuning Inhil in writing recount texts. The sample of the research was 40 students in the second grade of MA Darul Istiqomah Kemuning. The data were obtained from students’ ability in writing a recount text. The writing test was used as the test to assess the students’ ability. The time allocation was 60 minutes for the entire test. The data were scored by three raters by using writing scoring system that assesses five aspects of writing: content, grammar, organization, vocabulary and mechanics. The finding showed that the students had a good ability level in writing recount texts which means that students were able to write the recount text in English well. It was found out that the students’ ability in terms of content was the highest among other aspects with the category score level is good and the lowest score was in terms of mechanics with the category score level is fair. From the findings, it is suggested the students need to do more practice in writing English texts and improve their writing especially in terms of grammar and mechanics.Key Words: Ability, Writing, Recount Text